Power of Sentences in Foreign Language Classes - Mozhgan Alsadat Ghaffarzadeh Hassankiadeh (International Journal of Evaluation and Research in Education (IJERE), 2013)
Memorizing and rote learning are the simplest ways to get mark, but they won't help learners to use what they have memorized. In fact, learners will carry out a huge amount of knowledge but they can't apply them. In this study a powerful and important tool is introduced to solve the problem in Iranian classes. And it is utilizing sentences. In this article, a flowchart of sentence plan, which was constructed to aid learners in applying what they have learned, was included. The study highlights the importance of sentences in learning a language and introduces playing as an effective procedure to assist learners in learning how to construct correct sentences.DOI: http://dx.doi.org/10.11591/ijere.v2i2.1668